Wide horizons: science and epic in Mina Loy's ‘Anglo-Mongrels and the Rose’ and C. Day Lewis's From Feathers to Iron - Whitworth, M (Taylor & Francis, 2023)
Both Mina Loy's autobiographical poem ‘Anglo-Mongrels and the Rose’ and C. Day Lewis's From Feathers to Iron are cognizant of epic without reproducing the conventions of epic narrative. In part, the epic quality of both comes from their depiction or implication of epic scales as a backdrop for human action. Unfamiliar scales were found in many sciences, with astronomy and cosmology being the most prominent in the early twentieth century. The essay considers Loy's scientific diction and Day Lewis's sources in popular science and astronomy works by A. S. Eddington and James Jeans.